Psychosocial workplace factors as predictors of health outcomes among Health workers - ADU, Richard Akinjide; SHENGE, Nyitor Alexander (Journal of Psychology and Allied Disciplines, 2024)
This research examined psychosocial workplace factors (self-esteem, work autonomy, role overload and role conflict) as predictors of health outcomes (physical health, work-related mental health and general mental strain) in health workers in Ondo Medical Village, Ondo State, Nigeria. The study adopted correlational research design. One hundred and two participants, male (34) and female (68) health workers purposively sampled from five centres (Trauma, Mother and Child, Kidney Care Clinic, Ganni Fawehinmi Diagnostic, and Information) in Ondo Medical Village, Ondo State, Nigeria participated in the study. Data were collected from the respondents using seven validated scales with adequate psychometric properties. Three hypotheses were stated and tested using multiple regression analyses. The results of correlational analysis showed that, there was a significant relationship between sex and physical health (r = .29; p < .01) among the sampled participants. However, there was no significant correlation between sex and work-related mental health (r = .06; p > .05). Also, sex did not correlate significantly with general mental strain (r = -.14; p > .05). Furthermore, self-esteem, work autonomy, role overload, and role conflict jointly predicted general mental strain significantly [R2= .21, F (4, 97) = 6.34; p < .01]. This study concluded that, psychosocial workplace factors were significant predictors of health outcomes among the sampled health workers. It is recommended therefore, that, employers of labour and managers should take cognizance of these psychosocial workplace factors in their intervention programmes aimed at enhancing the health outcomes of their employees.